Enhancing the Effectiveness of the World Bank’s Global Footprint : An Independent Evaluation - World Bank (Washington, DC: World Bank, 2022)
*May 5, 2022: New version includes Green Sheet* The World Bank aims to further expand and adjust its global footprint by the mid-2020s, especially in lower-income countries and those affected by fragility, conflict, and violence (FCV). This first-of-its-kind evaluation assesses the effectiveness of the World Bank’s past decentralization efforts in a systematic way to inform the new expansion of the World Bank’s global footprint. Decentralization refers to the World Bank’s efforts to expand its global footprint by moving more staff, especially staff with operational and decision-making duties, to the field. The report examines the benefits and challenges of staff decentralization and makes recommendations to improve its process and outcomes, while also preserving the Bank’s global nature, which is one of its comparative strengths.